2014
DOI: 10.1186/1472-6963-14-459
|View full text |Cite
|
Sign up to set email alerts
|

Provider cost analysis supports results-based contracting out of maternal and newborn health services: an evidence-based policy perspective

Abstract: BackgroundThere is dearth of evidence on provider cost of contracted out services particularly for Maternal and Newborn Health (MNH). The evidence base is weak for policy makers to estimate resources required for scaling up contracting. This paper ascertains provider unit costs and expenditure distribution at contracted out government primary health centers to inform the development of optimal resource envelopes for contracting out MNH services.MethodsThis is a case study of provider costs of MNH services at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…In contrast the estimates from other countries have been considerably higher: $215 for Cuba, $39 for Thailand [ 8 ] and $ 35.8 in Argentina [ 18 ]. Studies that have considered a provider perspective presented results close to those of this study and to each other: the mean cost of antenatal care was $16 in Tanzania [ 19 ], $18 in Ghana [ 20 ], and $18.78 in Pakistan [ 21 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In contrast the estimates from other countries have been considerably higher: $215 for Cuba, $39 for Thailand [ 8 ] and $ 35.8 in Argentina [ 18 ]. Studies that have considered a provider perspective presented results close to those of this study and to each other: the mean cost of antenatal care was $16 in Tanzania [ 19 ], $18 in Ghana [ 20 ], and $18.78 in Pakistan [ 21 ].…”
Section: Discussionsupporting
confidence: 82%
“…This was consistent with results of Livin et al [ 9 ], who reported drugs and consumables as the main contributors to total ANC cost. However, other studies have reported human resources as the most costly input to antenatal care [ 18 , 19 , 21 ]. More generally, personnel is often reported as the input with the highest cost in primary health care [ 20 , 22 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies available at the time of the fieldwork (World Bank 2006a), as well as independent fieldwork conducted in the two districts (Faisalabad and Lodhran) where the program has been implemented, showed that PRSP was able to record dramatic improvements in performance: the problem of staff absenteeism disappeared, patient turnout improved, government-supplied medicines which in the past always seemed to be out of stock were now available, and all these improvements were recorded within the existing budget. International evaluations and research studies continue to note BHU privatization in Pakistan as a successful case of public-private partnership within the health sector for improved social-service delivery to the poor (Hatcher et al 2014).…”
Section: Three Apparent Successes But Only One Embedded Partnershipmentioning
confidence: 99%
“…It is also important how to collect data and calculate these indices. A study by Hatcher et al 34 in Pakistan examined the unit cost of 2 rural primary health centers that had been assigned to a private company. The results of the study showed that the unit costs of these centers were higher than expected.…”
Section: Indicators Examined To Determine the Project Success Ratementioning
confidence: 99%